Bangunan Fisik Rumah Sebagai Penyebab Kejadian Tuberkulosis Paru - Wildanny Nur Maulinda; Sri Hernawati; Ancah Caesarina Novi Marchianti (Multidisciplinary Journal, 2021)
Globally, the World Health Organization reported that there were 10.4 million cases of Pulmonary Tuberculosis in 2016. It is also estimated that many cases still have been undiagnosed or unreported. Meanwhile, 45% of pulmonary tuberculosis cases globally occur in Southeast Asia, including in Indonesia. After implementing strategies to reduce the prevalence of pulmonary TB, the reality showed that they had not succeeded significantly. It was due to the spread of pulmonary TB disease caused by several factors such as the house physical construction. Houses with unhealthy conditions can be a medium for transmitting respiratory disease. Therefore, this research objective was to analyze the effect of house physical construction on the pulmonary TB incidences in the work area of Primary Health Care of Tanggul, Jember Regency. The research design was a case-control using 57 respondents from the case group and 57 respondents from the control group as research samples. The data analysis used bivariate analysis with chi-square test. The results of the identification of respondents' characteristics on the components of the house (ceilings, walls, floors, windows, ventilation, kitchen smoke holes, and lighting), showed that most of them met the healthy housing standards based on healthful house parameters, both from control group and case group. Based on the results of bivariate data analysis with the chi-square test of 8 variables, one variables had significant effects on the pulmonary TB incidence is lighting.